The Effects of Magnet Hospitals on Nurse Outcomes: Systematic Review - Nurcan Bilgin; Dilek Özmen; Ezgi Bolat (Association of Nurse Managers, 2020)
ABSTRACT Aim: This study was aimed to examine the effects of magnet hospitals on nurse outcomes. Methods: Article searches were carried out using the PubMed and Scopus databases with different combinations of keywords including 'magnet hospitals', 'non-magnet hospitals', 'nursing' and 'nursing skill mix', 'nursing worked hours', 'nursing practice environment', 'missed nursing care'. As a result of the scanning, 102 articles that were published in international journals were reached. 8 articles from these articles met the inclusion criteria. Results: All of the 8 articles were descriptive comparative research types. The majority of studies included in this systematic review study, data were collected from the hospital or directly from nurses. For data collection; in addition to valid and reliable measurement tools, informations from national databases and questionnaires created by researcher/s were used. In the evaluated articles, nursing skill mix in three studies, nursing worked hours in two studies, nursing practice environment in four studies and missed nursing care in two studies were investigated. Conclusions: With the limited number of studies evaluated, it is possible to say that the magnet hospitals have better working environments, the levels of skill-mix of the nurses and missed nursing care are lower and there is no difference between working hours of hospitals. In order to obtain strong evidence, it is recommended to perform longitudinal, semi-experimental studies evaluating the effectiveness of magnet and non-magnet hospitals and randomization to prevent selection bias.